Can climate adaptation reduce conflict? What a decade of work in Jirapa, Ghana reveals about linking adaptation to stability - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
Climate adaptation can build peace, but only if we design for it. In Jirapa, Ghana between 2012–2021, a Climate Smart Village paired climate adaptation with conflict-sensitive development. Farmers helped co-design a bundle of improved seeds, weather advisories, agroforestry, market links, and microfinance, tackling both climate stress and social divides. When researchers later applied the CGIAR Climate Security Sensitivity Tool (CSST), they found stronger resilience and higher peace scores than in nearby villages, especially during Ghana’s 2022 economic crisis when fertilizer prices tripled. The lesson? Ignoring power dynamics can turn adaptation into maladaptation. Tools like the CSST help teams spot conflict risks early and design for peace from the start.